Clinical biomarkers in older patients with aortic stenosis - Anand, Atul (The University of Edinburgh, 2019)
The incidence of degenerative aortic stenosis is increasing with an ageing population. Valve replacement is the only proven treatment, but this carries significant procedural risk in older people. Current guidelines advocate intervention in symptomatic severe aortic stenosis, but non-cardiac symptoms and comorbidity may obscure this assessment. Clinical biomarkers offer the potential for objective patient assessment. My aim was to firstly assess the validity and reproducibility of novel blood biomarkers of disease progression in aortic stenosis. Secondly, in older patients considered for valve replacement, my aim was to compare measures of frailty with conventional surgical risk assessment. In 265 patients with asymptomatic aortic stenosis and 46 healthy controls, I assessed serum concentrations of the sarcomeric protein cardiac myosin binding protein C (cMyC) and objective markers of disease progression and mortality. cMyC concentrations were independently associated with imaging evidence of left ventricular mass, fibrosis volume and extracellular volume. These relationships were not observed in healthy controls. cMyC concentrations were also associated with all-cause mortality over 11 years of follow-up. This suggests a role for cMyC as a novel objective biomarker of aortic stenosis disease severity. Other blood biomarkers including cardiac troponin, brain-type natriuretic peptide (BNP) and galectin-3 have been suggested as disease biomarkers in aortic stenosis. However, performance and precision of these assays has not been described in older patients. In a study of analytical and biological variability, I undertook repeated hourly and weekly blood sampling for cardiac troponin, BNP and galectin-3 in 14 subjects with severe asymptomatic aortic stenosis. These biomarkers demonstrated low indices of individuality, implying that interpretation requires serial testing for change rather than isolated elevated blood concentrations. The reference change values for weekly fresh sampling were 42% for cardiac troponin, 55% for BNP and 14% for galectin. These values for cardiac troponin and BNP were lower than equivalent studies in healthy controls and in stable heart failure. To assess the role of frailty in the assessment of patients for aortic valve replacement, I first performed a systematic review and meta-analysis of studies including frailty assessment before Transcatheter Aortic Valve Implantation (TAVI). This procedure is reserved for patients considered at prohibitive risk of complication from conventional open-heart surgery. Ten cohort studies with 4,592 TAVI patients were included. Frailty was associated with increased risk of early and late mortality, and use of an objective frailty tool rather than subjective assessment identified those at highest risk; these patients experienced greater than double the mortality risk of non-frail individuals. In 185 patients with severe aortic stenosis, I prospectively assessed frailty using four tools: the Fried phenotype, Edmonton Frail Scale, Short Physical Performance Battery and Clinical Frailty Scale. These measures were compared to surgical risk assessment scores from the Society of Thoracic Surgeons (STS) and EuroSCORE II. Agreement between frailty measures was moderate and unrelated to patient age or the degree of aortic valve severity. Frail patients had poorer physical and mental wellbeing. Frailty increased at higher STS and EuroSCORE estimates, but using principal components analysis I demonstrated divergence between frailty measures and surgical risk estimates. Outcomes after aortic valve replacement are now required to establish if this observation is meaningful for the improved prediction of outcomes after surgery. My findings suggest that serial testing of blood biomarkers of myocardial injury in patients with aortic stenosis may detect meaningful disease progression prior to decompensation. In patients considered for valve replacement, measurement of frailty differs from existing surgical risk tools and may add to the holistic assessment of older patients.
Keywords: ageing; aortic stenosis; frailty; risk prediction